Abandoned corrals: colonization and vegetation recovery of ephemeral habitats in silvo-pastoral systems. (19th September 2020) - Vinograd, Arie; Zaady, Eli; Kigel, Jaime
Abstract: Aims: Management of silvo-pastoral systems in planted and natural forests in semi-arid Mediterranean regions often employs seasonal night corrals for animal protection. This management system changes the spatial distribution of animal excreta, resulting in a net transfer of soil mineral resources and their accumulation in the corrals. After abandonment, corrals are colonized by ruderal species, becoming focal sources for their spread in the forest. We aimed to implement a rational management of seasonal sheep corrals based on a better understanding of the vegetation processes occurring in abandoned corrals, in order to alleviate their negative impact in the forest. Methods: Relationships between temporal changes in the vegetation, the soil seed-bank and levels of soil nutrients were studied in a chronosequence of abandoned sheep corrals and compared with nearby reference plots in planted Eucalyptus forests grazed by sheep in the semi-arid North-Western Negev, Israel. The region has a bi-seasonal Mediterranean climate, with high dominance of annual species in the grazing range. Important Findings: Abandoned sheep corrals were colonized by seeds of ruderals originating in older abandoned corrals. Subsequent successional changes occur at a slow rate, driven by the depletion of soil resources in the abandoned corrals, and were still in progress 20 years after abandonment. Ruderals were gradually replaced, first by taller grasses and followed by short grasses, but most forbs and particularly geophytes did not recover during this period. Recovery of the original herbaceous vegetation in the corrals was through seed dispersal from the surrounding vegetation, not from the original soil seed-bank remaining in the corrals after abandonment. Ruderal species in the grazed, planted forests behave as patch-tracking metapopulations. Their persistency depends on constant creation of new corrals compensating for the gradually dwindling populations in older abandoned corrals, and on the availability of dispersal vectors.